2019
DOI: 10.3390/molecules24193473
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamomum cassia Presl: A Review of Its Traditional Uses, Phytochemistry, Pharmacology and Toxicology

Abstract: Cinnamomum cassia Presl is a tropical aromatic evergreen tree of the Lauraceae family, commonly used in traditional Chinese medicine. It is also a traditional spice, widely used around the world. This paper summarizes the achievements of modern research on C. cassia, including the traditional uses, phytochemistry, pharmacology and toxicology. In addition, this review also discusses some significant issues and the potential direction of future C. cassia research. More than 160 chemicals have been separated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(113 citation statements)
references
References 75 publications
(139 reference statements)
2
110
0
1
Order By: Relevance
“…C. verum extracts have strong anti-inflammatory [15] and antioxidant effects and improve reduced glutathione synthesis in the liver [35,36]. Such medicinal effects are useful because piroplasmosis infection is related to reactive oxygen and nitrogen species overproduction, which leads to oxidative stress [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. verum extracts have strong anti-inflammatory [15] and antioxidant effects and improve reduced glutathione synthesis in the liver [35,36]. Such medicinal effects are useful because piroplasmosis infection is related to reactive oxygen and nitrogen species overproduction, which leads to oxidative stress [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented antiseptic, antiviral, antibacterial, antifungal, antidiabetic, hypocholesteremic, carminative, astringent, and blood purifier activities [13,14]. Recently, Zhang et al [15] reported that C. cassia possesses many pharmacological activities, including antibacterial, anti-inflammatory, antitumor, anti-obesity, analgesic, antidiabetic, antiviral, cardiovascular protective, neuroprotective, cytoprotective and immunoregulatory properties. The effective role of cinnamon in the inhibition of different diseases is attributed to the presence of various chemical constituents in high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the names of the two drugs are similar, the drugs themselves are different. A. obliqua S. M. Hwang has a high content of aristolochic acid, which can cause a series of diseases, such as the apoptosis or necrosis of renal tubular epithelial cells and renal ischemia (Zhang et al, 2019).…”
Section: Misuse Of Hmmentioning
confidence: 99%
“…Furthermore, the addition of plant extracts could increase the biological potential of the obtained drinks. Cinnamon has antitumor, antiinflammatory, antidiabetic, antiobesity, antibacterial, antiviral, cardiovascular protective, cytoprotective, neuroprotective and immunoregulation activity [15].…”
Section: Introductionmentioning
confidence: 99%